Ventilated supercavity shapes and hydrodynamic characteristics of bow rudder layout. (July 2022) - Zhou, Shuning; Li, Daijin; Huang, Chuang; Xu, Haiyu
Abstract: To investigate the influence of bow rudders on ventilated supercavity shape and hydrodynamic characteristics, the unsteady numerical simulation is performed using the shear stress transport (SST) turbulence model and Singhal cavitation model. The results show that after bow rudders are configured, a secondary cavity is formed downstream the rudder and the shape of the mainstream supercavity is subsequently altered. Compared with the reference condition of 0° rudder angle, the rudder angle presents negligible effects on the shape of the mainstream supercavity, while the lateral rotating deformation of the cavity near the rudder is also observed. For ventilated conditions, the pressure on the suction surface of the rudder does not reduce indefinitely as the rudder angle increases. When the suction surface is fully cavitated, the pressure is approximately the same as that of the mainstream supercavity. A linear relationship is found between hydrodynamic characteristics of bow rudders and the rudder angle less than 8°. However, the hydrodynamic force linearity and efficiency of bow rudders decrease when the rudder angle is larger than the critical value.